Shared measures : collective performance data use in collaborations - Kroll, Alexander (Cambridge : Cambridge University Press, 2022)
Traditionally, performance metrics and data have been used to hold organizations accountable. But public service provision is not merely hierarchical anymore. Increasingly, we see partnerships among government agencies, private or nonprofit organizations, and civil society groups. Such collaborations may also use goals, measures, and data to manage group efforts, however, the application of performance practices here will likely follow a different logic. This Element introduces the concepts of "shared measures" and "collective data use" to add collaborative, relational elements to existing performance management theory. It draws on a case study of collaboratives in North Carolina that were established to develop community responses to the opioid epidemic. To explain the use of shared performance measures and data within these collaboratives, this Element studies the role of factors such as group composition, participatory structures, social relationships, distributed leadership, group culture, and value congruence.
Title from publisher's bibliographic system (viewed on 21 Feb 2022).
Keywords: Performance -- Measurement; Performance -- Data processing; Performance -- Management; Big data; Cooperation